(untitled) (Universal International Scientific Journal, 2026)
This scientific article analyzes the effectiveness of using artificial intelligence-based analytical systems in international trade processes based on a deep scientific, theoretical and practical approach. In the digital economy, the complexity of trade operations, the expansion of global supply chains, and the increase in real-time information flow require the improvement of analytical decision-making tools. The study reveals the role of AI-analytical tools in forecasting accuracy, risk assessment, logistics optimization, market situation determination, and the formation of trade strategies. Methodologically, the methods of systematic analysis, comparison, generalization of empirical results, and review of scientific sources were used. The results show that AI-based analytical systems are emerging as an important tool in increasing trade efficiency, reducing costs, and ensuring strategic stability.